On the role of interference in laser-based mid-infrared widefield microspectroscopy - Schönhals, Arthur; Kröger-Lui, Niels; Pucci, Annemarie; Petrich, Wolfgang (Journal of biophotonics, 2018)
A laser's high degree of coherence leads to interferences, which—in the absence of precautions—can cause severe image distortions such as fringes and speckles and which thereby strongly hamper a meaningful interpretation of hyperspectral images in laser-based widefield microspectroscopy. While images and spectra of homogenous samples may already suffer from interferences, any structured object such as a tissue thin section will add to these distortions due to wavelength- and, in particular, sample-dependent phase shifts (structure sizes, absorption coefficients, refractive indices). This effect is devastating for the universal applicability of laser-based microspectroscopy especially in the mid-infrared (MIR), where cell sizes are of the same dimension as the wavelength of the illumination source. Here, we show that the impact of interferences is strongly mitigated by reducing the time-averaged spatiotemporal coherence properties of the illumination using a moving plus a stationary scatterer. In this case, the illumination path provides a pseudothermal radiation source and spatially resolved spectra can be obtained at the quality of the reference method, that is, Fourier-transform infrared microspectroscopy, without compromising spectral or spatial resolution.
Gesehen am 22.04.2020